Measurement of electrons from open heavy-flavor hadron decays in pp at s = 13 TeV and electrons from beauty-hadron decays in Pb-Pb at sNN = 5.02 TeV collisions by ALICE at LHC - Conti, Camila de (2019)
In this thesis it is performed the measurement of electrons from heavy-flavor hadron decays, with the use of the ALICE detector, at LHC. Two analysis are performed. The first one consists in the measurement of the invariant cross section of electrons from open heavy-flavor (charm or beauty) hadron decays in pp collisions at s = 13 TeV, the largest center of mass energy generated by LHC up to now, in the transverse momentum interval 0.5 < pT < 4 GeV/c. The experimental cross-section is compared to the pQCD-based prediction given by FONLL, and it sits on the upper edge of the theoretical uncertainty band over the full momentum range. The ratios between this experimental result and the equivalent measurements performed at lower center of mass energy have the potential to bring constrains to the FONLL calculation. The second analysis consists in the measurement of the nuclear modification factor, RAA , of electrons from beauty-hadron decays in the 10% most central Pb-Pb collisions at sNN = 5.02 TeV, in the interval 2 < pT < 8 GeV/c. Electrons from beauty-hadron decays are extracted from the inclusive electron yield via fits to the impact parameter distribution using templates of electrons from different sources, obtained from Monte Carlo simulations. This measurement allows to probe the energy loss of beauty quarks when traversing the Quark-Gluon-Plasma (QGP), a color-deconfined medium produced in relativistic heavy-ion collisions. A suppression of about 40-50% is observed on the RAA for pT > 3 GeV/c and it is consistent, over the full momentum range and within experimental uncertainties, with the prediction of pQCD-based models that describe a mass-dependent energy loss of the heavy-quarks while traversing the QGP, interacting with its constituents via radiative and collisional processes. This analysis brings significant improvement of the experimental uncertainties with respect to the equivalent measurement performed with the run 1 data and consists in an important step in the study of the mass-dependence of the energy loss of heavy quarks inside the QGP at low pT .